Organocatalytic Multicomponent Reactions of 1,3-Dicarbonyls for the Synthesis of Enantioenriched Heterocycles - Du, Haiying; Dudognon, Yohan; Sanchez Duque, Maria del Mar; Goudedranche, Sébastien; Bonne, Damien; Rodriguez, Jean; Bugaut, Xavier; Constantieux, Thierry (Synthesis, 2016)
In this feature article, a general perspective of the research program aimed towards the preparation of polycyclic heterocycles by the means of enantioselective organocatalytic multicomponent reactions is presented. Guidelines for reaction design, including the selection of substrates and organocatalysts are discussed. For all transformations, scope and limitations are presented, along with post-functionalization to afford diversified heterocyclic scaffolds.1 Introduction2 Type I Products: 1,4,5,6-Tetrahydropyridines3 Type II Products: 1,2,3,4-Tetrahydropyridines4 Type III Products: Bridged Perhydropyridines5 Conclusion and Perspective
Keywords: 1,3-dicarbonyls; enantioselectivity; heterocycles; Michael addition; multicomponent reactions; organocatalysis